A Top-Down Clustering and Cluster-Tree-Based Routing Scheme for Wireless Sensor Networks. (2nd May 2011) - Bandara, H. M. N. Dilum; Jayasumana, Anura P.; Illangasekare, Tissa H.
Abstract : Cluster-based organization of large sensor networks is the basis for many techniques aimed at enhancing power conservation and network management. A backbone network in the form of a cluster tree further enhances routing, broadcasting, and in-network processing. We propose a configurable top-down cluster and cluster-tree formation algorithm, a cluster-tree self-optimization phase, a hierarchical cluster addressing scheme, and a routing scheme. Such self-organization makes it possible to effectively deliver messages to a sink as well as within the network. For example, a circular sensor field with a sink in the center can establish cross-links and circular-paths within the cluster tree to deliver messages through shorter routes while reducing hotspots and consequently increasing network lifetime. Cluster and cluster-tree formation algorithm is independent of physical topology, and does not require a priori neighborhood information, location awareness, or time synchronization. Algorithm parameters allow for formation of cluster trees with desirable properties such as controlled breadth/depth, uniform cluster size, and circular clusters. Characteristics of clusters, cluster tree, and routing are used to demonstrate the effectiveness of the schemes over existing techniques.